Studi Prevalensi Gangguan Fungsi Paru dan Jumlah Kunjungan ke Poliklinik Karyawan Unit Sining 5 dan Bagian CCR Pt. Apac Inti Corpora - Wardani, Tatiek Dyah; Suhartono, Suhartono; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Backgroud: PT. Apac Inti Corpora as a textile factory has different cotton dust level in each unit. At spinning 5 unit which has 0,29 mg/m3 – 0,83 mg/m3 dust level is lower than CCR unit which has 5,036 mg/m3dust level. The difference of dust level will caused various level of risk. Higher prevalence of lung function disorder will increase number of patient that equivalence with number of visitors in polyclinic.  The aim of this study is to observe the different of lung function disorder patient’s distribution and number of visitors in polyclinic between employee in spinning 5 and CCR at PT. Apac Inti Corpora. Method: This research used cross sectional design. It was used  simple random sampling technique and took 100 people with 50 people each location. Result: This study showed that 12 people (24%) of workers at spinning 5 had a lung function disorder and 10 people (20%) at CCR. Even though workers at spinning 5 had lower dust level than CCR. Based on statistics test the difference of prevalence lung function disorder is not significant p=0,631. Based on the medical report in polyclinic during 2008,  we found that all patients dad a lung function disorder. In fact, no difference amount of visitors between spinning 5 with CCR in PT. Apac Inti Corpora (p=0,489). Keywords: prevalence of lung function disorder, PT. Apac Inti Corpora